OBSERVATIONS OF IMPACT-INDUCED MOLTEN METAL-SILICATE PARTITIONING - Rowan L.R.; Ahrens T.J. (My University, 1994)
Observations of molten mid-ocean ridge basalt (MORB)-molybdenum (Mo) interactions produced by shock experiments provide insight into impact and differentiation processes involving metal-silicate partitioning. Analysis of fragments recovered from experiments (achieving MORB liquid shock pressures from 0.8 to 6 GPa) revealed significant changes in the composition of the MORB and Mo due to reaction of the silicate and metal liquids on a short time scale ( < 13 s). The FeO concentration of the shocked liquid de creases systematically with increasing pressure. In fact, the most highly shocked liquid (6 GPa) contains only 0.1 wt% FeO compared to an initial concentration of 9 wt% in the MORB. We infer from the presence of micrometer-sized Fe-, Si- and Mo-rich metallic spheres in the shocked glass that the Fe and Si oxides in the MORB were reduced in an estimated oxygen fugacity of 10^(−17) bar and subsequently alloyed with the Mo. The in-situ reduction of FeO in the shocked molten basalt implies that shock-induced reduction of impact melt should be considered a viable mechanism for the formation of metallic phases. Similar metallic phases may form during impact accretion of planets and in impacted material found on the lunar surface and near terrestrial impact craters. In particular, the minute, isolated Fe particles found in lunar soils may have formed by such a process. Furthermore, the metallic spheres within the shocked glass have a globular texture similar to the textures of metallic spheroids from lunar samples and the estimated, slow cooling rate of ⩽ 140°C/s for our spheres is consistent with the interpretation that the lunar spheroids formed by slow cooling within a melted target.